Expression of CK-19 Immunomarker in Thyroid Neoplasm and its Association with Histopathology (TAJ: Journal of Teachers Association, 2022)
Background & Objective: Early and accurate diagnosis of thyroid neoplasm is of utmost significance for prolongation of patient survival. A panel of immunomarkers has been tested to overcome the limitation of histopathology. CK-19 is a commonly used immunomarker among them. This study was undertaken to evaluate the diagnostic accuracy of CK-19 in thyroid neoplasm.Methods & Materials: This cross-sectional study was conducted in the Department of Pathology, Rajshahi Medical College, over a period of two years, from July 2017 to June 2019. A total of 44 tissue blocks of histologically confirmed thyroid neoplasm were included in this study. Then immunohistochemistry was done for CK-19 from a significant paraffin-embedded block.Result: In the present study, diffuse and strong positivity of CK-19 was found in papillary thyroid carcinoma (PTC), followed by focal positivity in follicular(FC) and medullary carcinoma (MC). A negative staining pattern was found in all cases of follicular adenoma (FA). The sensitivity and specificity of CK-19 were found to be high in the case of PTC, respectively, 88% and 92%.CK-19 expression was highly specific in differentiating malignant from benign thyroid tumors (100%).Conclusion: The study concluded that CK 19 is a highly sensitive and specific marker in papillary thyroid carcinoma. Diffuse and strong positivity is characteristic of PTC, which can be used in diagnosis with equivocal morphological appearance.TAJ 2022; 35: No-1: 01-06